Insomnia in migraine patients: impact on disability, depression, and anxiety - a partial analysis - Sakamoto, Karina Hikari; Campos, Gabriela Rosa; Frederico, Regina Célia Poli; Oliveira, Carlos Eduardo Coral de; Reiche, Edna Maria Vissoci; Bello, Valéria Aparecida; Silva, Aline Vitali da (Headache Medicine, 2024)
Introduction: Migraine is a complex neurological disorder with profound interactions with the body’s homeostasis, particularly the sleep-wake cycle. Objective: To evaluate the effect of sleep parameters on individuals with migraine and their association with migraine severity and mood. Methods: This is a cross-sectional study involving 49 participants diagnosed with migraine and treated at the Headache Clinic of PUC-PR, Londrina-PR, Brazil. Demographic, anthropometric, and clinical data were collected, along with responses to validated questionnaires: Migraine Disability Assessment (MIDAS), Headache Impact Test (HIT-6), 12-item Allodynia Symptom Checklist (ASC-12), General Anxiety Disorder-7 (GAD-7), Beck Depression Inventory (BDI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESE), and Morningness-Eveningness Questionnaire (MEQ). Spearman’s correlation was used to examine the relationships between variables, considering statistical significance for p<0.05. Results: The study participants were predominantly female (69.4%) with a median age of 36 (27-47) years. Chronic migraine was present in 35 (71.4%) participants, 11 (22.4%) were using preventive medications, and 24 (49.0%) had medication overuse. The most common chronotype was intermediate (49.0%), followed by morning (44.9%) and evening (6.1%). Moderate to severe insomnia was identified in 10 (20.4%) and excessive daytime sleepiness in 15 (30.5%) participants. There was a strong correlation between insomnia and depressive symptoms (ρ=0.555; p<0.001; R²=0.308), as well as between insomnia and anxiety symptoms (ρ=0.521; p<0.001; R²=0.271). Additionally, there was a moderate correlation between insomnia and migraine-related disability (ρ=0.302; p=0.035; R²=0.091) and insomnia with age (ρ=0.331; p=0.02; R²=0.109). Conclusion Sleep disorders are common among individuals with migraine and impact their mood and migraine-related disability. Key-words: Insomnia, Migraine, Depression, Anxiety.